2012
DOI: 10.1016/j.expneurol.2011.11.040
|View full text |Cite
|
Sign up to set email alerts
|

HIF-1α is neuroprotective during the early phases of mild hypoxia in rat cortical neurons

Abstract: Hypoxia-inducible factor 1α (HIF-1α) is a transcription factor that plays a key role regulating the adaptive response to hypoxia. HIF-1α is stabilised during hypoxia and, after dimerization with HIF-1β, triggers the expression of different genes involved in cell cycle control and energy metabolism associated with cell survival. However, HIF-1α also regulates the expression of proapoptotic genes. The aim of this work is to ascertain the influence of HIF-1α on neurotoxicity evoked by hypoxia in rat cortical neur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
27
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 41 publications
(31 citation statements)
references
References 47 publications
(37 reference statements)
3
27
1
Order By: Relevance
“…Depletion of HIF-1α in the mouse brain and in neuronal cell cultures causes increased cell damage and lower survival rate after cerebral ischemia (Baranova et al, 2007). In rat cortical neurons, HIF-1α appears to play a protective role in early steps of responses to mild hypoxia (Lopez-Hernandez et al, 2012). HIF-1α has recently been shown to regulate prion protein expression in hippocampal neuronal cells to protect from cell damage (Jeong et al, 2012).…”
Section: Key Molecules Involvedmentioning
confidence: 99%
“…Depletion of HIF-1α in the mouse brain and in neuronal cell cultures causes increased cell damage and lower survival rate after cerebral ischemia (Baranova et al, 2007). In rat cortical neurons, HIF-1α appears to play a protective role in early steps of responses to mild hypoxia (Lopez-Hernandez et al, 2012). HIF-1α has recently been shown to regulate prion protein expression in hippocampal neuronal cells to protect from cell damage (Jeong et al, 2012).…”
Section: Key Molecules Involvedmentioning
confidence: 99%
“…However, this neuroprotective effect seems to be transitory. For instance, HIF‐1α protects neurons from apoptosis during the early phase of chemical hypoxia or from mild hypoxia but, under prolonged hypoxia, the neuroprotective effect was lost and neurons eventually die from apoptosis (Posadas et al ., ; Lopez‐Hernandez et al ., ). These findings suggest that additional mechanisms are involved in determining neuronal survival or death at the later stages of hypoxia.…”
Section: Introductionmentioning
confidence: 99%
“…It has been observed that oxidative stress can cause neurodegeneration associated with enhanced susceptibility to apoptosis due to the activation of pro-apoptotic genes (Gibson and Huang 2002;Du et al 2012). Hypoxia-induced oxidative stress can cause neurite retraction leading to neurodegeneration and neuronal loss similar to that found in Alzheimer's disease (Banasiak et al 2000;de la Monte et al 2000;Yeh et al 2008;Prentice et al 2011;López-Hernández et al 2012).…”
Section: Introductionmentioning
confidence: 88%